Generation of temperature-sensitive human metapneumovirus strains that provide protective immunity in hamsters - Herfst, Sander; de Graaf, Miranda; Schrauwen, Eefje J. A; Sprong, Leo; Hussain, Karim; van den Hoogen, Bernadette G; Osterhaus, Albert D. M. E; Fouchier, Ron A. M (Journal of general virology, 2008)
Department of Virology, Erasmus Medical Center, Rotterdam, The Netherlands Correspondence Ron A. M. Fouchier r.fouchieraterasmusmc.nl Human metapneumovirus (HMPV) causes acute respiratory tract illness primarily in young children, immunocompromised individuals and the elderly. Vaccines would be desirable to prevent severe illnesses in these risk groups. Here, we describe the generation and evaluation of cold-passage (cp) temperature-sensitive (ts) HMPV strains as vaccine candidates. Repeated passage of HMPV at low temperatures in Vero cells resulted in the accumulation of mutations in the viral genome. Introduction of these mutations in a recombinant HMPV by reverse genetics resulted in a ts-phenotype, judged on the decreased shut-off temperature for virus replication in vitro . As an alternative approach, three previously described cp-respiratory syncytial virus (cp-HRSV) mutations were introduced in a recombinant HMPV, which also resulted in a low shut-off temperature in vitro . Replication of these ts-viruses containing either the cp-HMPV or cp-HRSV mutations was reduced in the upper respiratory tract (URT) and undetectable in the lower respiratory tract (LRT) of hamsters. Nevertheless, high titres of HMPV-specific antibodies were induced by both ts-viruses. Upon immunization with the ts-viruses, the LRT of hamsters were completely protected against challenge infection with a heterologous HMPV strain, and URT viral titres were reduced by 10 000-fold. In conclusion, we provide proof-of-principle for two candidate live-attenuated HMPV vaccines that induce cross-protective immunity to prevent infection of the LRT in Syrian golden hamsters. Further mapping of the molecular determinants of attenuation of HMPV should be the subject of future studies. Published online ahead of print on 24 April 2008 as DOI 10.1099/vir.0.2008/002022-0.